The Fragility of Agricultural Landscapes and Resilience of Communities to Landslide Occurrence in the Tropical Humid Environments of Kigezi Highlands in South Western Uganda - Nseka, Denis; Bamutaze, Yazidhi; Mugagga, Frank; Nakileza, Bob (Springer, Cham., 2019)
This chapter examines the influence of agricultural land uses on the occurrence of landslides in the humid tropical environments of Kigezi highlands in South Western Uganda. Analysis of the agricultural land use practices is a prerequisite to understanding landscape fragility and community resilience to landslide hazards. An analysis of agricultural land use patterns was undertaken through interpretation of Sentinel 2A images for 2016. The imagery data was acquired from the European Space Agency (ESA) Sentinels Scientific Data Hub. Field surveys and investigations were also carried out to establish and map the spatial distribution of landslide hazards. Six agricultural land use categories were identified, namely, annuals, perennials, grazing, fallow, wood lots and agroforestry. Considering the agricultural land use patterns, annual crops are the dominant agricultural land use type spanning 69% of the total area followed; by perennials (13%). Grazing land and fallows covered 11% and 5%, respectively. The study revealed that annual crop land is the most affected agricultural land use category. Out of the 65 landslide scars mapped, 31% occurred on annual crop areas. Wood lot areas experienced the least landslide occurrence (4%). A close spatial distribution of agricultural land use practices and landslide occurrence is discernible. It is recommended that a comprehensive tree planting campaign be carried out in areas prone to landslides since it was inferred that wood lots suffered least from landslides. It is also recommended that farmers be encouraged to restore and manage terrace bunds which could help to check on water velocity and consequently increase on slope stability.
Keywords: Agricultural land uses; Landslides; Tropical environments